Hybrid Learning in VUCA Times: Keeping The Balancing Act Between Aiming Ideal Expectations and Managing The Realities - Putu Ayu Sutaningrat Puspa Dewi (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
The most needed thing during a pandemic is empathy. People need to be intellectually, emotionally, physically and socially aware that every individual has their own battle. This paper avoids being very prescriptive when discussing possible solutions. Hybrid learning has been the way of learning in the transition from school closure to reopening the school period. There are three important things to be remembered when entering the journey of seeking the best solutions. First, having the right mindset that students are the core of our business. Everyone shall take aside their interest and move only under the interest of delivering the rights of our students in learning. Second, teachers are key actors at the school level. They design, enable and execute the learning for the students. Therefore, it is a moral responsibility of everyone to support teachers’ role as instructional leaders. Lastly, there are no uniform solutions nor the same recipe for all schools. Thus, each school can optimise hybrid learning in this changing situation by balancing their ideal expectations and realities.